"Light-assisted evaporation induced self-assembly": an efficient approach toward ordered carbon materials. Issue 4 (10th December 2014) - Ghimbeu, Camélia Matei; Soprony, Mihai; Sima, Felix; Vaulot, Cyril; Vidal, Loïc; Le Meins, Jean-Marc; Delmotte, Luc
Abstract : The synthesis of ordered porous carbons by a green, simple and rapid approach based on light exposure of a solution of carbon precursors and a soft-template, in the presence or not of a photosensitizer is demonstrated herein along with their formation mechanism. Abstract : The synthesis of ordered porous carbons by a green, simple and rapid approach based on light exposure of a solution of carbon precursors and a soft-template in the presence or not of a photosensitizer is demonstrated herein along with their formation mechanism. The influence of the benzophenone amount on the formation of phenolic resin and the carbon structure, morphology and textural properties was systematically studied. The polymerization, self-assembly and carbonization are promoted in the same step by light. The benzophenone accelerates several times the reaction rate modifying mainly the phenolic-resin structure (higher degree of cross-linking and carbonization) via radical formation, as highlighted by Raman spectroscopy. In addition, the increase of benzophenone amount gradually induces the modification of carbon morphology from a worm-like disordered structure to a highly organized hexagonal one while the surface area and pore volume remain unchanged. The 13 C and 1 H solid state and relaxation NMR analysis pointed out that this behavior is triggered by the different micellar structuration of the template in the presence of benzophenone, the phenolic-resin composition involving only carbon precursor derived compounds and not benzophenone.